Enacting Order in Online Mathematics Classrooms: An Ethnomethodological Study - Simons, Marius (Advances in Social Sciences Research Journal, 2026)
This study investigates how order is enacted and maintained in online undergraduate mathematics classrooms through the lens of ethnomethodology. Conducted on the backdrop of the COVID-19 pandemic in South Africa, the research explores how learners and lecturers navigated the interactional demands of virtual learning spaces. Drawing on data from recorded lessons, chat transcripts, and semi-structured interviews across three higher education institutions, the study identifies practices that sustain interactional order, including tacit turn-taking, repair mechanisms, and the negotiation of shared reference frames. The findings reveal that online mathematics classrooms are socially co-constructed spaces where order is actively produced through mutual accountability, adaptive performances, and collaborative repair work. The study contributes to a deeper understanding of the sociological dynamics of mathematics education in digital contexts. It offers insights for developing socially responsive online pedagogies in South African higher education.